2013
DOI: 10.1128/aem.03063-12
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction of Fe(III) under Alkaline Conditions Relevant to Geological Disposal

Abstract: To determine whether biologically mediated Fe(III) reduction is possible under alkaline conditions in systems of relevance to geological disposal of radioactive wastes, a series of microcosm experiments was set up using hyperalkaline sediments (pH ϳ11.8) surrounding a legacy lime working site in Buxton, United Kingdom. The microcosms were incubated for 28 days and held at pH 10. There was clear evidence for anoxic microbial activity, with consumption of lactate (added as an electron donor) concomitant with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 53 publications
(49 reference statements)
3
68
1
1
Order By: Relevance
“…To explore the biogeochemistry of uranium under anoxic conditions at pH 10−10.5, microcosms were established using calcite dominated sediment and groundwater (SI Table S1 and ref 18 for mineralogical information) from a high pH lime workings site in the U.K. and similar to past work. 18 There was a progression of microbial redox processes in both the no added Fe(III) and with added Fe(III) microcosms which were maintained at pH 10−10.5 ( Figure 1A,B). For the no added Fe(III) system, nitrate, which was present at low but measurable concentrations (53 μM), dropped rapidly after incubation, and was below the limit of detection after 3 days.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To explore the biogeochemistry of uranium under anoxic conditions at pH 10−10.5, microcosms were established using calcite dominated sediment and groundwater (SI Table S1 and ref 18 for mineralogical information) from a high pH lime workings site in the U.K. and similar to past work. 18 There was a progression of microbial redox processes in both the no added Fe(III) and with added Fe(III) microcosms which were maintained at pH 10−10.5 ( Figure 1A,B). For the no added Fe(III) system, nitrate, which was present at low but measurable concentrations (53 μM), dropped rapidly after incubation, and was below the limit of detection after 3 days.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, it is speculated that the iron reduction mechanisms of alkaliphilic bacteria must be extremely efficient. Recently, it has been shown that adding riboflavin to a community of alkaliphilic soil bacteria grown in vitro at pH 10 increased the rate at which Fe(III) was reduced, suggesting that members of the community might be able to use riboflavin as an electron shuttle under alkaline conditions (46). However, as electron shuttle-catalyzed reactions are very pH sensitive (38,39), it may not be appropriate to extrapolate what is known about the process from studies performed at nearly neutral pH to high-pH environments.…”
mentioning
confidence: 99%
“…Recently it was shown that a clear succession of electron acceptor utilization existed in alkaline microcosm cultures up to pH 11, as rapid nitrate reduction was followed by slower soluble Fe(III)-citrate, insoluble Fe(III)-oxyhydroxide, and sulfate reduction (Rizoulis et al 2012). Further sediment microcosm studies from our group have also shown that alkaline bioreduction of Fe(III)-oxyhydroxide can lead to the formation of magnetite (Williamson et al 2013) and that microbially mediated reduction of U(VI) can occur at pH 10 (Williamson et al 2014).…”
Section: Potential For Metal Reduction At Alkaline Phmentioning
confidence: 72%